Spread of quarantine plant pests in Ukraine - Holiachuk, Yu.; Kosylovych , H. (Quarantine and plant protection, 2024)
Goal. Of article is analyse of spreading dynamics of insect species with the quarantine status for Ukraine territory based on data of the State Service of Ukraine on Food Safety and Consumer Protection. Methods. The work used official data on the distribution of plant quarantine organisms, which were interpreted using the analytical and comparative method of research. Results. The development of insect species with status of locally presented (list A-2 of the List of regulated harmful organisms) and species with status of absent (list A-1) in Ukraine was detected during 2015—2023. By data of State Service of Ukraine on Food Safety and Consumer Protection, the areal of American white moth, western corn rootworm and South American tomato moth have increased, while the spreading area of potato moth, and western flower thrips have decreased. These species have status of locally presented in Ukraine. The Mediterranean fruit fly belongs to list A-1, but its spreading area was detected in Odessa region during 2015—2023, and from 2022, some increase of spreading was noted. State Service of Ukraine on Food Safety and Consumer Protection fixes the increasing of tobacco whitefly (list A-1) area. The rapid spread of emerald ash borer are noted in Ukraine from 2019, and brown marmorated stink bug are presented in Ukraine in 2023. Conclusions. According to the results of the analysis of the distribution of quarantine insect species, an increase in the areas inhabited by American white moth, western corn rootworm, South American tomato moth, Mediterranean fruit fly, tobacco whitefly, as well as the appearance of the previously absent emerald ash borer and brown marmorated stink bug on the territory of Ukraine were established. In order to prevent the spread of quarantine pests, business entities whose activities may contribute to the spread of quarantine organisms must strictly adhere to the state policy in the field of plant quarantine.